Molar Buccal Tubes Front and Back Openings Dimensions and Torsional Play - Al-Zubaidi, Hiyam J; Alhuwaizi, Akram F (Journal of Baghdad College of Dentistry, 2018)
Background/: Buccal tubes are orthodontic attachments used on the posterior teeth instead of bands, so it is important to focus on the effect of their properties on orthodontic treatment. The aims of the present in vitro study are to evaluate and compare the buccal tube front and back openings dimensions and the torsional play angle of six different brands. Materials and Methods: The samples consisted of Single bondable, non-convertible first molar buccal tubes from six brands supplied from six companies (Dentaurum, Forestadent, Ormco, 3M, American Orthodontic, A-Star). Regarding tube opening dimension, ten buccal tubes of each brand were examined by an optical microscope. Each tube was fixed during examination using synthetic mud and oriented for observation of the front and back slot openings. A picture was taken for both tube openings and the result appeared on the computer’s screen where width and height measurements were made. While regarding torsional play angle, ten buccal tubes of each brand were used. Each tube was fixed on a metal block attached to a surveyor base. Then an L-shaped wire was inserted inside the front opening of the tube. Two photographs were taken, one with the wire in free fall position and the other with the wire elevated by a 10g weight with the same angle of shooting as the first photograph. Later, the two images were superimposed in Adobe Photoshop program, and an electronic MB-ruler Software was used to calculate the angle which represents the torsional play within each tube. The data were then statistically analyzed using ANOVA and LSD tests. Results: There are marked differences between measured tube dimensions and the manufacturer stated dimensions with the front tube openings being generally larger than the back opening dimensions. Furthermore, the torsional play angle was highest in A-Star and smallest in Ormco’s tubes. This angle was significantly correlated to the height of the tube front opening. Conclusion: It can be concluded that tube dimension varies among different companies and effect greatly torsional play angle.